(untitled) (World Bulletin of Public Health, 2024)
Pterygium is a common ocular surface disorder characterized by the growth of fibrovascular tissue over the cornea. This article provides a comprehensive overview of pterygium histology, including its pathogenesis, cellular components, and molecular characteristics. Understanding the histological features of pterygium is crucial for developing effective treatment strategies and improving patient outcomes.